Coach or sensei? His group relations in the context of tradition - Cynarski Wojciech J. (Sciendo, 2020)
In the perspective of the General Theory of Fighting Arts, an analysis of socio-cultural factors that determine the opposition of the role of a teacher of martial arts (Jap. sensei) to the role of a sports trainers was undertaken. The structural cultural context, cultural patterns, and social institutions resulting from divergent goals were taken into account. The roles of teachers and trainers result from these conditions. The existence of the separate roles of the master-teacher in martial arts and the sports trainer was established. These roles manifest themselves in different relations with students or players. Democratic and egalitarian interactions in sports teams include player and coach relations. In traditional martial arts, the dominance of the teacher is more accepted. However, there is also a social position combining the features of the sensei and the trainer that is typical for combat sports that are also martial arts (participating in sports competitions). As there are relationships of subordination in the hierarchical societies of Japan and Korea, there is no problem with recognizing the primary role of the sensei in these cultures. The position of the master-teacher is also sanctified by tradition. Reducing educational systems, which are the paths of martial arts, to oriental varieties of sports would be a serious factual mistake.